Mathematical Analysis of Continuum Mechanics and Industrial Applications III Proceedings of the International Conference CoMFoS18 - Itou, Hiromichi; Hirano, Shiro; Kimura, Masato; Kovtunenko, Victor A.; Khludnev, Alexandr M.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book focuses on mathematical theory and numerical simulation related to various areas of continuum mechanics, such as fracture mechanics, (visco)elasticity, optimal shape design, modelling of earthquakes and Tsunami waves, material structure, interface dynamics and complex systems. Written by leading researchers from the fields of applied mathematics, physics, seismology, engineering, and industry with an extensive knowledge of mathematical analysis, it helps readers understand how mathematical theory can be applied to various phenomena, and conversely, how to formulate actual phenomena as mathematical problems. This book is the sequel to the proceedings of the International Conference of Continuum Mechanics Focusing on Singularities (CoMFoS) 15 and CoMFoS16.
Fracture Mechanics -- Elasticity -- Shape Optimization and Inverse Problems -- Earthquake and Tsunami.
Keywords: Mechanics; Mechanics, Applied; Mathematical models; Natural disasters; Computer simulation; Solid Mechanics; Mathematical Modeling and Industrial Mathematics; Natural Hazards; Simulation and Modeling